DIALEKTIKA ORIENTASI GERAKAN SOSIAL KEAGAMAAN (ISLAM) DI INDONESIA - Ahmad Faqih (At-Taqaddum, 2011)
The religious social movement in a sociological perspective, is a natural process as the response of each group of man to face the social change occurred. It may also be caused by the strong desire of every human groups to seek change that is expected. Muslims in Indonesia in facing the demands of the objective in accordance with his time/periode, and the demands of the doctrine appeared/created the social movement to confront and resolve the social problems that exist. Both of these differences resulted the various of Islamic social movements that suited with the characteristic and social dynamics that occur in his time/periode.When we see the orientation at  the beginning of the emergence of socioreligious movement, on the 19th and the early 20th century, the type of movement more closely with religious social movements emerged/appeared as a reaction against to the Dutch colonialsm. The Dutch colonial’s periode for 3,5 centuries, has caused the suffering of indigenous (asli/pribumi) people in all facets of life. As known in history, that the religious social movement with the struggle orientation against the colonial was achieved/succeed with a declaration of independence which is the proclamation of independence on August 17, 1945. Based on this success, the orientation of religious social movements shifted from the orientation of the struggle orientation to be the practical politics. This is a logical consequence of the long struggle by the majority of Muslims throughout the country.The dialectic of religious social movement orientation always happened history of Indonesia with the advantages and disadvantages that must be faced. So that, it is difficult for us to justify if right or wrong of any orientation chosen by the Muslims is every phase of history.